Realisasi Bantuan Alat Mesin Pertanian Kepada Subak (Kasus Pelaksanaan Program Upaya Khusus Peningkatan Produksi Padi Jagung dan Kedelai di Subak Penginyahan Desa Puhu Kecamatan Payangan Kabupaten Gianyar) - I NYOMAN USADI PRADNYANA; I DEWA PUTU OKA SUARDI; A.A.A WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
The Realization of Agricultural Machinery Aid To Subak(Implementation Case of Special Effort Program Enhancement of RiceCorn and Soybeans Production in Subak Penginyahan, Puhu Village ofPayangan District, Gianyar) Indonesia is one of agricultural country and most of the citizen work in agriculturesector but in some recent years Indonesia always import food from other countries, toprevent this from happening continuously in 2015, the government makes a specialeffort progarm (Upsus) enhancement of rice, corn, and soybeans production in 2017is expected that Indonesia has reached food self-sufficiency, Upsus program hassome kind of aids like agricultural equipment and machine aid (Alsintan) that isexpected to simplify and speed up the production process.This study aims to find out(1) To find out the suitability of the proposed agricultural machinery aid (Alsintan)proposed by Subak Penginyahan; (2) To find out the use of agricultural machinerywhich is Subak Penginyahan recieved.The location of this research is located inSubak Penginyahan, Puhu Village, Payangan District, Gianyar Regency. Populationof this research is 70 active members of Subak Penginyahan. Sample size wasdetermined using Nottoadmojo formula, so the number of respondents who weretaken 41 people and added with 1 respondent from Agriculture Department ofGianyar Regency, 1 PPL respondent who in charge at Penginyahan Subak and 1respondent from Pekaseh Subak Penginyahan.The result of this study indicates thatthe realization of Alsintan aid in Subak Penginyahan is not suitable as purposed.There are differences in numbers and types of Alsintan that is proposed with receivedby Subak. For Alsintan type received by Subak is alsintan hand tractor type with thisthe realization of Alsintan aid that is purposed by Subak is suitable with what isproposed by Subak. Based on findings of the research that the writer conducted, itcan be suggested to the government to increase its attention to the farmercontinuously; In this case to continue aids provision that could help and provoke theenthusiasm of farmers to farm.